Observations on Insects Visiting Flowers of Cherimoya and Atemoya in Sicily (ltaly) (Bollettino di zoologia agraria e bachicoltura, 2024)
As an inadequate pollination is one of the factors limiting the commercial production of Annona spp. in many countries, observations on insects visiting flowers of Cherimoya (Annona cherimola Mili.) and Atemoya (A . cherimola x A. squamosa L.) were carried out in Campobello di Mazara (Trapani) and Sciacca (Agrigento) (Sicily), in 1995. All the insects which visited flowers were surveyed and most of them identified. 44,6% and 20,5% of flowers were visited by insects in Campobello di Mazara and Sciacca respectively. Nine species of insects were collected in the first orchard: among them the staphylinid Paraphloeostiba gayndahensis (McLeay), the nitidulid beetle Carpophilus tersus Wollaston, and the thrip Frankliniella occidentalis (Pergande) represented 87.4% of all the insects found inside flowers; the most abundant species in Sciacca was the anthocorid Orius laevigatus (Fieber) (70.3%). In 1996 branches of some custard-apples (A. cherimola cv Fino de Jete) were covered with sleeves inside which specimens of O. laevigatus were released. The species had a positive influence on the pollination of Annona as the percentage of fruit set was similar to that obtained in the uncovered control. The percentage of well formed fruits was however lower than the one obtained in the uncovered control.
Keywords: Annona spp.; insects; flowers; Sicily; pollination